2003
DOI: 10.1007/s00784-003-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salivary pellicle formation time on enamel demineralization – an in situ pilot study

Abstract: This study assessed the protective potential of salivary pellicles formed in situ over periods ranging from 2 to 24 h. Pellicles were produced on enamel slabs mounted on the palatal aspect of removable acrylic splints and exposed to the oral environment in three subjects for 2, 6, 12 and 24 h. Enamel specimens with and without pellicles were immersed in citric acid (1%) for 60 s, and the amount of dissolved calcium was measured by atomic absorption spectroscopy. In addition, specimens were processed for transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1
34

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 12 publications
4
86
1
34
Order By: Relevance
“…Therefore, determination of dental enamel dissolution by assessing the amount of calcium or phosphate dissolved from the apatite crystals of dental hard tissue could also be regarded as a possible tool for assessing dental erosions. Hence, some authors had applied calcium determina-tion in erosive, acidic solutions after prolonged contact (range 2 min to 24 h) of the solutions with dental hard tissue using calcium sensitive electrodes, atomic adsorption spectrophotometer or the highly sensitive method of inductively coupled plasma mass spectrometry [68][69][70][71][72] Calcium-sensitive electrodes often need a specific pH of the environment to work precisely. Additionally, cal-cium complexes formed with certain acids (e.g.…”
Section: Chemical Analysis Of Minerals Dissolved In the Erosive Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, determination of dental enamel dissolution by assessing the amount of calcium or phosphate dissolved from the apatite crystals of dental hard tissue could also be regarded as a possible tool for assessing dental erosions. Hence, some authors had applied calcium determina-tion in erosive, acidic solutions after prolonged contact (range 2 min to 24 h) of the solutions with dental hard tissue using calcium sensitive electrodes, atomic adsorption spectrophotometer or the highly sensitive method of inductively coupled plasma mass spectrometry [68][69][70][71][72] Calcium-sensitive electrodes often need a specific pH of the environment to work precisely. Additionally, cal-cium complexes formed with certain acids (e.g.…”
Section: Chemical Analysis Of Minerals Dissolved In the Erosive Agentmentioning
confidence: 99%
“…Then a slice (50-200 tJm) is prepared perpendicular to the surface the same way as for tradi-tional TMR. Thereby, both depth of the erosive crater and the depth below the bottom of the crater at which mineral content was reduced (surface softening) can be assessed with TMR giving lesion depth and integrated Methods for Assessment of Dental Erosion 11 mineral loss as variables [89,90] [42] [67,68]. In these studies, TMR was used to record lesion depths from 20 tJm and more.…”
mentioning
confidence: 99%
“…They also noted that short term exposure to phosphoric or citric acid could completely remove the protective pellicle. Later on, Hannig et al 11 (2003) demonstrated that a salivary pellicle only 3 minutes old conferred protection to enamel against citric acid attack. They demonstrated that the pellicle is 20-500 nm thick within the first two hours of exposure to saliva, depending on location, and is resistant to removal by a toothbrush (without toothpaste) and masticatory forces.…”
Section: Introductionmentioning
confidence: 99%
“…Uma vez que diferentes ácidos variam na sua capacidade de desmineralizarem o esmalte bovino , a proteção da película formada in situ na erosão do esmalte e da dentina causada pelos ácidos hidroclórico, cítrico e fosfórico foi analisada (WIEGAND et al, 2008 (HANNIG, M. et al, 2004;HANNIG, M. et al, 2003). A proteção média (30,5%) obtida para a dentina combinando os resultados dos 3 diferentes tipos de ácidos (WIEGAND et al, 2008) está de acordo com resultado de um estudo prévio , que encontrou uma redução da perda de cálcio da ordem de 27% após o tratamento com ácido hidroclórico (pH 2,3, 5 minutos).…”
Section: Composição Da Película Adquiridaunclassified
“…Pode-se assumir que diferenças na estrutura do esmalte e da dentina poderiam afetar a composição da película adquirida (GLANTZ; BAIER; CHRISTERSSON, 1996) e, desta maneira, o seu potencial protetor, que é atribuído à sua habilidade em agir como uma barreira de difusão ou uma membrana semipermeável (HANNIG, M. et al, 2003). A maior porosidade e solubilidade da dentina comparada ao esmalte leva a uma desmineralização mais rápida, o que pode impedir que a película aja como uma barreira protetora (HARA et al, 2006).…”
Section: Composição Da Película Adquiridaunclassified